2014
DOI: 10.1590/0034-737x201461060006
|View full text |Cite
|
Sign up to set email alerts
|

Seletividade de produtos naturais comerciais a Trichogramma pretiosum (Riley, 1879) (Hymenoptera: Trichogrammatidae)

Abstract: A seletividade de produtos naturais a parasitoides é pouco conhecida. Em vista disso, este trabalho teve por objetivo avaliar a seletividade de produtos naturais comerciais a Trichogramma pretiosum Riley (Hymenoptera: Trichogrammatidae). Os produtos utilizados foram Baicao®, Orobor® e Topneem®, nas concentrações recomendadas pelos fabricantes, e pulverizados sobre cartelas contendo ovos esterilizados de Anagasta kuehniella Zeller (Lepidoptera: Pyralidae). Teste com chance de escolha para parasitismo foi realiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
3
1
Order By: Relevance
“…The orange oil fertilizer (Orobor) reduced the T. podisi parasitism, different from that found by Luckmann et al (2014), in similar study with T. pretiosum. This difference between the results for the tests with orange oil fertilizer can be attributed to the parasitoid species being different, because, as Filho et al (2006) mentioned, various species of natural enemies of pests respond differently to natural products.…”
Section: Discussioncontrasting
confidence: 82%
See 3 more Smart Citations
“…The orange oil fertilizer (Orobor) reduced the T. podisi parasitism, different from that found by Luckmann et al (2014), in similar study with T. pretiosum. This difference between the results for the tests with orange oil fertilizer can be attributed to the parasitoid species being different, because, as Filho et al (2006) mentioned, various species of natural enemies of pests respond differently to natural products.…”
Section: Discussioncontrasting
confidence: 82%
“…In contrast, Smaniotto et al (2013) found that Natuneem did not cause a repellent effect on T. podisi parasitism and also did not affect the offspring percentage of emergence in the pre-and post-parasitism tests. In the same way, Luckmann et al (2014) did not observe reduction in the parasitism of T. pretiosum when Topneem was applied in preparasitism tests. It also did not cause mortality of the larval stage parasitoid during the post-parasitism test.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations